Introduction to probability and stochastic processes with applications - Blanco Castañeda, Liliana (Wiley, 2012)
"This text book is designed for a one-year course in probability and stochastic processes with applications, especially for students who wish to specialize in probabilistic modeling. This book bridges the gap between elementary texts and advanced texts in probability and is easily accessible for students with diverse backgrounds and majoring in engineering, applied sciences, business and finance, statistics, mathematics, and operations research. The text contains many examples and exercises which have been tested in classrooms and are chosen from diverse areas such as queuing models, reliability and finance. Chapter coverage includes: basic concepts; random variables and their distributions; discrete distributions; continuous distributions; random vectors; multivariate normal distributions; conditional expectation; limit theorems; stochastic processes; queuing models; stochastic calculus; and mathematical finance"--